#1**+5 **

r=3cos(Theta) ...... and to convert to Cartesian form, we have

√(x^2 + y^2) = 3 (x)/√(x^2 + y^2) simplify

(x^2 + y^2) = 3x subtract 3x from both sides

x^2 - 3x + y^2 = 0 complete the square on x

x^2 - 3x + 9/4 + y^2 = 9/4 factor

(x - 3/2)^2 + y^2 = 9/4

Here is a graph of both forms......https://www.desmos.com/calculator/xty6odyy4z

(Notice that they are the very same graph !!!!)

CPhill
Dec 15, 2014

#1**+5 **

Best Answer

r=3cos(Theta) ...... and to convert to Cartesian form, we have

√(x^2 + y^2) = 3 (x)/√(x^2 + y^2) simplify

(x^2 + y^2) = 3x subtract 3x from both sides

x^2 - 3x + y^2 = 0 complete the square on x

x^2 - 3x + 9/4 + y^2 = 9/4 factor

(x - 3/2)^2 + y^2 = 9/4

Here is a graph of both forms......https://www.desmos.com/calculator/xty6odyy4z

(Notice that they are the very same graph !!!!)

CPhill
Dec 15, 2014